1984
DOI: 10.1016/0014-5793(84)81326-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipopolysaccharide on lipid bilayer permeability of β‐lactam antibiotics

Abstract: The lipid-bilayer permeability of cephalosporins was extensively suppressed by addition of lipopolysaccharide to liposomal membrane in proportion to the hydrophobicity of the drugs. This suggests that the polysaccharide chain layer contributes to the barrier function. The importance of the polysaccharide chain in the barrier function was also supported by the fact that the permeability to Rd-type lipopolysaccharide-containing liposomes showed essentially the same dependency on the hydrophobicity of the cephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…Several hypotheses can explain how LPS modulates Gram-negative outer envelope permeability. Nikaido and coworkers have suggested that the carbohydrate moiety would act as a barrier against hydrophobic molecules (25), thus explaining why the permeativity of some antibiotics (e.g., cephalosporins) is proportional to their hydrophobicity (19). In fact, X-ray diffraction studies suggest that LPS thickness (i.e., its polysaccharide content) is inversely proportional to outer membrane permeability (29), supporting the aforementioned hypothesis (25).…”
Section: Discussionmentioning
confidence: 87%
“…Several hypotheses can explain how LPS modulates Gram-negative outer envelope permeability. Nikaido and coworkers have suggested that the carbohydrate moiety would act as a barrier against hydrophobic molecules (25), thus explaining why the permeativity of some antibiotics (e.g., cephalosporins) is proportional to their hydrophobicity (19). In fact, X-ray diffraction studies suggest that LPS thickness (i.e., its polysaccharide content) is inversely proportional to outer membrane permeability (29), supporting the aforementioned hypothesis (25).…”
Section: Discussionmentioning
confidence: 87%
“…The occurrence of negatively charged phosphate groups, decorating most LPS macromolecules, contributes to the structure and the low fluidity of the LPS monolayer, because they engage in electrostatic interactions with divalent cations such as calcium (Ca 2+ ) and magnesium (Mg 2+ ) normally present on the surface of the OM . This is reflected in bacterial resistance to harsh conditions, as in the case of extremophiles, as well as in the case of bacteria exposed to dangerous external compounds, such as antibiotics . A plethora of other features characterizing the LPS structure have been demonstrated to be involved in the capability of the bacteria to resist stress factors .…”
Section: Lpss From Gram‐negative Mesophilic Bacteria: Overviewmentioning
confidence: 99%
“…[12][13][14][15] This is reflected in bacterial resistance to harsh conditions, as in the case of extremophiles, as well as in the case of bacteria exposed to dangerous external compounds, such as antibiotics. [29] A plethora of other features characterizing the LPS structure have been demonstrated to be involved in the capability of the bacteria to resist stress factors. [12][13][14][15] Given the wide structural heterogeneity of LPS structures, it is reasonable to assume that the external environment is one of the key drivers in promoting such high structural diversity.…”
Section: Lpss From Gram-negative Mesophilic Bacteria: Overviewmentioning
confidence: 99%
“…The contribution of LPS to the barrier effect has been demonstrated with E. coli [38], but not with Bacteroides spp. [39].…”
Section: Reduced Antibiotic Penetrationmentioning
confidence: 99%